Pengaruh Westernisasi Terhadap Mahasiswa Teknik Lingkungan 2022 Kelas C UPN â€œVeteranâ€ Jawa Timur - Kinanti R. Hayati; Naafi Rachmattullah R; Dicky Kartika B.S; Evan Yafi B (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This study examines the awareness of Westernization among Environmental Engineering students of Class C in the 2022 cohort at UPNVJT and their understanding of its impact on Indonesia. Westernization is a process of imitating cultural practices from other countries, particularly Western countries, and is associated with adopting a Western lifestyle. The findings indicate that these students are aware of the strong influence of Westernization in Indonesia and recognize its negative consequences. Despite being personally affected by Westernization, they possess the ability to filter unwanted information and demonstrate awareness of the benefits and drawbacks of Westernization in the Indonesian context.